2013
DOI: 10.2308/jmar-50397
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Examination of Diversification and Firm Productivity

Abstract: The advantages and disadvantages of diversification have been widely debated by academics, as well as business professionals, and the majority of studies suggest that diversification destroys firm value. The effect of overall diversification (without categorizing whether such diversification is related or unrelated to the business) on productivity has been investigated as well, but with similar conflicting results. In this paper, we investigate the effects of the two types of diversification on productivity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…The BCC model estimates the production efficiency scores of the firms in the Compustat database, and the second stage relates the production efficiency scores to our strategy variables. We follow Chang et al [21] in our choice of input and output variables. We consider three inputs and one output in the DEA model.…”
Section: Measuring Production Efficiency Using Data Envelopmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The BCC model estimates the production efficiency scores of the firms in the Compustat database, and the second stage relates the production efficiency scores to our strategy variables. We follow Chang et al [21] in our choice of input and output variables. We consider three inputs and one output in the DEA model.…”
Section: Measuring Production Efficiency Using Data Envelopmentmentioning
confidence: 99%
“…DEA measures the relative production efficiency relative to all other firms in the dataset. Therefore, we follow Chang et al [21] and partition our main dataset into the different industry categories, using the Fama-French 12 industry classification 2 . This enables us to estimate DEA for each industry dataset separately and compute efficiency scores for each firm relative to similar firms in the same industry.…”
Section: Measuring Production Efficiency Using Data Envelopmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Balsam et al (2011) showed that firms pursuing cost leadership strategy are able to put more emphasis on the executive compensation for increasing sales volume and by lowering price. Chang et al (2013) showed that derived ratios, such as sales, general and administrative cost per sales, R&D expense per sales, sales per cost of goods sold, etc., generated from such cost elements are inevitable to distinguish cost leaders from the differentiators. These variables are indeed under the control of the management.…”
Section: Introductionmentioning
confidence: 99%